Seasonal Variations in the Protein content from Different tissues of Octopus aegina in Pazhayar coastal waters, Nagapattinam District, Tamilnadu - Kavitha, S.; Ponni, A. Christy (International Journal of Scientific Research in Biological Sciences, 2018)
Of all the components, changes in protein play an important role in the seasonal variation of the chemical composition. In general, the water content of the tissue of bivalves usually gives an indication of the time of spawning. Variation in dry tissue weight of mollusc is always associated with biochemical components. Seasonal changes in the biochemical constituent are the characteristics of the seasonal activities of Molluscs. The present study was carried out on Octopus aegina to assess the seasonal variations in the protein content during January 2017 to December 2017. The total protein was estimated in muscle, gill, liver and gonad. The highest concentration of protein content was present in gonad followed by muscle, gill and liver. Among the seasonal changes, protein values were high during monsoon.